PENGARUH RASIO KEUANGAN, PENERAPAN PSAK 50 & 55 (REVISI 2006), MANAJEMEN LABA DAN PERANAN GOOD CORPORATE GOVERNANCE TERHADAP RETURN SAHAM - Rahil I. Aprilian; Yvonne Augustine (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
We examine the effects of financial ratios, implementation of PSAK 50 and 55 (Revised 2006), Earning Management and the Role of Good Corporate Governance (GCG) on Stock Return. The financial ratios used in this research are Capital Adequacy Ratio (CAR), Percentage of Operating Expense to Operating Revenue and Loan to Deposit Ratio (LDR). Earning management is measured by allowance for impairment losses and GCG as variable that moderated earning management and stock return, this research also used dummy variable for implementation of PSAK 50 and 55. This research used 26 listed banking companies in Indonesia Stock Exchange from 2008 to 2011. Total observation of research is 80 years financial statements. The result showed that (1) the financial ratio that has significant influence on stock return is CAR; (2) earning management and GCG didn’t have significant influence on stock return, but the earning management that moderated by GCG has significant influence on stock return; (3) implementation of PSAK 50 and 55 didn’t have significant influence on stock return; (4) All variable simultaneously made significant influence on stock return at 10% error.